2001
DOI: 10.1021/op000024q
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency by Design:  Optimisation in Process Research

Abstract: Experimental design (Box, G. E. P.; Hunter, W. G.; Hunter, J. S. Statistics for Experimenters; Wiley: New York, 1978 and Carlson, R. Design and Optimisation in Organic Synthesis; Elsevier: Amsterdam, 1992) is an established and proven methodology for product and process improvement in the pharmaceutical industry. This paper presents a step-by-step approach to optimisation of a synthetic transformation using a central composite experimental design, in conjunction with automated on-line HPLC. Highly predictive m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(44 citation statements)
references
References 2 publications
0
44
0
Order By: Relevance
“…[44] The preliminary study outlined above suggested that cross-coupling reactions involving aryldisiloxanes are affected by many variables; thus a traditional systematic optimisation process would be expected to be an extremely lengthy endeavour. [44] In addition, optimisation using a traditional approach is known to provide only a partial exploration of the overall "reaction space" (the full range of all the H NMR spectroscopic analysis of the isolated mixture of 17 and the corresponding homocoupled product after flash column chromatography. NA = no evidence for formation of the desired product by LCMS and 1 H NMR spectroscopic analysis of the crude reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…[44] The preliminary study outlined above suggested that cross-coupling reactions involving aryldisiloxanes are affected by many variables; thus a traditional systematic optimisation process would be expected to be an extremely lengthy endeavour. [44] In addition, optimisation using a traditional approach is known to provide only a partial exploration of the overall "reaction space" (the full range of all the H NMR spectroscopic analysis of the isolated mixture of 17 and the corresponding homocoupled product after flash column chromatography. NA = no evidence for formation of the desired product by LCMS and 1 H NMR spectroscopic analysis of the crude reaction mixture.…”
Section: Resultsmentioning
confidence: 99%
“…Traditionally, statistical experiments require full randomization to eliminate systematic errors that can create bias in the results. [11] However, we have found that waiting for heating and cooling of the reactor is the biggest contributor to the total optimization time, and that randomization did not lead to any difference in experimental results. Therefore it was decided that a higher intensification of experiments could be achieved with ascending ordering of temperature.…”
Section: Online Quantitative Mass Spectrometry For the Rapid Adaptivementioning
confidence: 81%
“…This a three-step approach still using the Baye- The Utility values for each design are also compared. Four di¡erent kinetic systems are compared: cell transport [3], continuous culture [7], drug transport [8] and receptor binding [9].…”
Section: Cell Transport Kinetics: Using a Bayesian Experimentalmentioning
confidence: 99%